The definitive guide to Catalyst : writing extensible, scalable, and maintainable Perl-based Web applications - Diment, Kieren; Trout, Matt S. (Berkeley, Calif. : Apress, 2009)
Provides information on creating Web applications using Perl.
Includes index.
Keywords: Perl (Computer program language); Perl (Computer language)